PENGARUH BAURAN PROMOSI TERHADAP KUNJUNGAN WISATAWAN DOMESTIK (STUDI KASUS DI TAMAN REKREASI SENGKALING MALANG) - Widayanti, Rahayu (DINAMIKA DOTCOM, 2012)
Many countries rely on tourism as a source of tax and revenue for companies selling services to tourists. Development of the tourism industry is one of the strategies used by private organizations to promote a particular region as a regional tour to promote trade through the sale of goods and services to non-local people. Besides the tourism sub-sector was expected to drive the economy, because the sector is considered the most prepared in terms of facilities, facilities and infrastructure compared to other business sectors. These expectations were developed in a community empowerment strategy through the development of populist-based tourism. The purpose of this study were: (1). To analyze whether the marketing mix consists of advertising, personal selling, sales promotion, public relations and simultaneously have an influence on the domestic tourist visits. (2). To analyze whether the marketing mix consists of advertising, personal selling, sales promotion, public relations and partially have an influence on the domestic tourist visits, (3). To analyze which marketing mix variables that have a dominant influence on the domestic tourist visits.This study uses data interval while the primary data collection through questionnaires to the 82 domestic touristswho visit the Recreation Park Sengkaling Malang. There are four independent variables are analyzed, namely: advertising, personal selling, sales promotion and public relations. While the dependent variable is the domestic tourist visits. The data has been collected then analyzed using multiple linear regression analysis. The results indicate that advertising, personal selling, sales promotion, public relations and simultaneously positively affect domestic tourists to visit. Variable partial advertising, personal selling, sales promotion, public relations and also in a positive and significant effect. Advertising variable is the dominant variable affecting the city. Keywords: advertising, personal selling, sales promotion, public relations, and employee requests